The importance of exercise and dimension factors in assessment centers: Simultaneous examinations of construct-related and criterion-related validity - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2009)
This study presents a simultaneous examination of multiple evidential bases of the validity of assessment center (AC) ratings. In particular, we combine both construct-related and criterion-related validation strategies in the same sample to determine the relative importance of exercises and dimensions. We examine the underlying structure of ACs in terms of exercise and dimension factors while directly linking these factors to a work-related criterion (salary). Results from an AC (N = 753) showed that exercise factors not only explained more variance in AC ratings than dimension factors but also were more important in predicting salary. Dimension factors explained a smaller albeit significant portion of the variance in AC ratings and had lower validity for predicting salary. The implications of these findings for AC theory, practice, and research are discussed.